2022
DOI: 10.1007/s10534-022-00477-3
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin for the prevention of COVID-19 infection in health care personnel: a double-blinded randomized clinical trial (LF-COVID)

Abstract: Lactoferrin (LF) has in vitro antiviral activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study aimed to determine the effect of bovine lactoferrin (bLF) in the prevention of SARS-CoV-2 infection in health care personnel. A randomized, double-blinded, placebo-controlled clinical trial was conducted in two tertiary hospitals that provide care to patients with SARS-CoV-2 infection in Lima, Peru. Daily supplementation with 600 mg of enteral bLF versus placebo for 90 days was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to a recent clinical trial, bLF supplementation (600 mg/day) did not ensure the total protection of the care personnel of a hospital against SARS-CoV-2 infection. 259 SARS-CoV-2 symptoms were confirmed in 11 out of 104 participants (10.6%). Nor was any evident effect observed during a 30 day treatment of SARS-CoV-2 infected patients with a daily dose of 800 mg of bLF.…”
Section: Biological Potential Of Lf Moleculementioning
confidence: 95%
See 1 more Smart Citation
“…According to a recent clinical trial, bLF supplementation (600 mg/day) did not ensure the total protection of the care personnel of a hospital against SARS-CoV-2 infection. 259 SARS-CoV-2 symptoms were confirmed in 11 out of 104 participants (10.6%). Nor was any evident effect observed during a 30 day treatment of SARS-CoV-2 infected patients with a daily dose of 800 mg of bLF.…”
Section: Biological Potential Of Lf Moleculementioning
confidence: 95%
“…On the contrary, in vivo results were not satisfactory enough. According to a recent clinical trial, bLF supplementation (600 mg/day) did not ensure the total protection of the care personnel of a hospital against SARS-CoV-2 infection . SARS-CoV-2 symptoms were confirmed in 11 out of 104 participants (10.6%).…”
Section: Biological Potential Of Lf Moleculementioning
confidence: 99%
“…Lactoferrin has been tested in the clinic for the treatment of COVID becaus antiviral activity, immunomodulatory properties, and safety profile. Such studi garnered highly varied and controversial results, ranging from no observed e symptom resolution in all treated patients [43][44][45][46][47]. This variation can likely be att to methodological differences, including but not limited to the delivery method (i sal spray or oral), type (liposomal or non-liposomal lactoferrin), endpoints, dosag of dosage relative to illness onset, and in one study, use of anti-inflammatory adj With only a 30% reduction in viral replication in vitro, it is not expected that tre Both diphenhydramine and lactoferrin are safe for oral consumption by adult humans.…”
Section: Antiviral Drug Combinations For Covidmentioning
confidence: 99%
“…Thus, Lf was reported as possessing a potential role in the prevention, treatment, and recovery from COVID-19 infections. Navarro et al ( 2022 ) evaluated the effects of bLf on COVID-19 infections in hospital settings in a clinical trial, but their results showed no significant effects of bLF on COVID-19 infection incidence, severity and symptoms in hospital personnel. However, liposomal bLf was used through oral and intranasal administration in COVID-19 in patients with mild-to-moderate disease and in COVID-19 asymptomatic patients; this work suggested a potential role for bLf as significant decreases in serum ferritin, IL-6, and D-dimers levels were seen (Campione et al 2021 ).…”
mentioning
confidence: 99%